The Development of Research Competency Measures for Learning Development of Teacher Students in Multicultural Southern Border Provinces: A Design-Based Research - Luangrangsee, Pol; Topithak, Krittyakan (Hatyai Academic Journal, 2022)
Aim of this research is to development of research competency measures for learning development of teacher students in multicultural southern border provinces by using design-based research methods. The research results factor and indicators of research competency measures for learning development of teacher students in multicultural southern border provinces have 3 factor, 13 indicators which are competencies in knowledge of research in a multicultural society have 5 indicators, competencies in skill of research in a multicultural society 5 indicators, and competencies in personal attribute 3 indicators. Which has the following analysis results; The research knowledge competency test form in a multicultural society, 15 items with difficulty between .32-.72 and discrimination from .20 and above. For research skills in a multicultural society, 15 items had inter-rater reliability mean between the .899-.952 and personal characteristics, 9 items had inter-rater reliability mean between .913-.959, statistically significant .05 level. And from examination construct validity by second order confirmatory factor analysis, It was found that the model was consistent with the empirical data.